2004
DOI: 10.1182/blood-2003-12-4146
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the volume of the immune response: strength and persistence of stimulation determine migration and cytokine secretion of dendritic cells

Abstract: Migration to lymph nodes and secretion of cytokines are critical functions of mature dendritic cells (DCs); however, these 2 functions are not necessarily linked. This is the first report showing that quantitative differences in identical signaling pathways determine DC migration and cytokine secretion. Using different polymerized forms of CD40 ligand, we demonstrate that the strength and persistence of CD40 signaling can induce either function. Induction of monocyte-derived DC (MoDC) migration required a weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 41 publications
4
74
0
Order By: Relevance
“…Similar to the effect of PGI 2 analogs, PGE 2 has been shown to inhibit IL-12, TNF-␣, and IL-6 production by BMDCs, suppress MHC class II expression, and enhance IL-10 production (22,29,38,39). Studies showed that DCs may be activated to produce high levels of proinflammatory cytokines and remain at sites of inflammation or develop into CCR7-expressing cells that allow them to migrate to the draining lymph nodes and induce Ag-specific immune responses (50,51). These migratory DCs produce low levels of inflammatory cytokines (50).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the effect of PGI 2 analogs, PGE 2 has been shown to inhibit IL-12, TNF-␣, and IL-6 production by BMDCs, suppress MHC class II expression, and enhance IL-10 production (22,29,38,39). Studies showed that DCs may be activated to produce high levels of proinflammatory cytokines and remain at sites of inflammation or develop into CCR7-expressing cells that allow them to migrate to the draining lymph nodes and induce Ag-specific immune responses (50,51). These migratory DCs produce low levels of inflammatory cytokines (50).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that DCs may be activated to produce high levels of proinflammatory cytokines and remain at sites of inflammation or develop into CCR7-expressing cells that allow them to migrate to the draining lymph nodes and induce Ag-specific immune responses (50,51). These migratory DCs produce low levels of inflammatory cytokines (50). PGE 2 promotes the generation of the migratory DCs, inhibits proinflammatory cytokine production (50), and up-regulates CCR7 expression (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of MAP kinases and other signal transduction pathways are important upstream events for the induction of DC maturation, migration or cytokine secretion [1,30]. Analysis of key intracellular signalling molecules in Ctx-stimulated MoDC revealed ERK1/2-activation, but no regulation of JNK or NFκB activity.…”
Section: Discussionmentioning
confidence: 99%